Sexual Behavior for HIV Prevention among Men who Have Sex with Men in Surakarta - Latifah Nur Alifia; Hermanu Joebagio; Bhisma Murti (Journal of Health Promotion and Behavior, 2018)
Background: To date HIV/AIDS is still a serious global health problem with an ever-increasing incidence. HIV risk in men who have sex with men (MSM) is 27 times greater than in the general population. This study aimed to analyze the sexual behavior for HIV prevention among MSM in Surakarta using the Health Belief Model (HBM).Subjects and Method: This was a qualitative analytical study with a phenomenology approach. It was carried out in Surakarta Mahardhika Style Community, Central Java. The key informants in this study were the Chairperson of the Gaya Mahardhika Community, with their members as the main informants. The supporting informants consisted of health personnel from the Prevention and Control Program at the City Health Office, and the Surakarta City AIDS Commission Informants were selected for this study by purposive sampling. The data were collected by in-depth interview, non-participatory observation, and document observation. The data were analyzed by the method of Miles and Huberman.Results: MSM communities in Surakarta understood the concept of HIV/AIDS and knew how to prevent it. But in reality, the prevention behavior has not really been done as evidenced by all the main informants having more than one partner. Nevertheless, all informants stated that they always used condoms and always checked voluntary counseling test (VCT) regularly. MSM communities consider themselves at risk, believe that HIV/AIDS is a dangerous disease, feel the benefits of HIV/AIDS prevention measures carried out. The obstacles faced are lack of comfort when using condoms and difficulties to be loyal to one partner. They feel the importance of HIV/AIDS preventive behavior. They are sure to be able to implement HIV/AIDS preventive behavior.Conclusion: Knowledge of HIV/AIDS risk factors is important. The HIV/AIDS preventive behavior applied by MSM is influenced by knowledge, perceived severity, perceived vulnerability, perceived benefit, perceived barrier, cues to action, and self-efficacy.Keywords: HIV prevention, men who have sex with men, Health Belief ModelCorrespondence: Latifah Nur Alifia. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, Surakarta, Central Java 57126, Indonesia. Email: Latifahnuralifia@gmail.com. Mobile: 08562623045.Journal of Epidemiology and Public Health 2018, 3(3): 179-191https://doi.org/10.26911/thejhpb.2018.03.03.05